Leveling Up Vocabulary: Exploring The Impact of Memrise on EFL Learners’ Word Power - Berlin Medi Pratama; Annisyah Rusman; Darmawan Budiyanto (Indonesian Language Education and Applied Linguistics Reviews, 2025)
This study investigates the effectiveness of the Memrise application in enhancing students’ English vocabulary mastery in an Indonesian EFL context. Employing a quasi-experimental design, 60 high school students were divided into two groups: an experimental group that received instruction through Memrise and a control group taught with conventional methods. Both groups were assessed using pre-tests and post-tests, and additional data were gathered through observation checklists and student questionnaires. The results of normality and homogeneity tests confirmed that the data met the assumptions for parametric testing. A paired sample t-test revealed a significant improvement in vocabulary scores within the experimental group, while the independent sample t-test indicated a statistically significant difference in vocabulary gains between the experimental and control groups in favor of the former. Students using Memrise demonstrated greater engagement and consistency, and their positive perceptions further supported the application’s usability and motivational value. These findings suggest that integrating Memrise into vocabulary instruction can significantly enhance vocabulary acq uisition, offering practical insights for language educators seeking to incorporate mobile-assisted learning into the classroom.